Pendidikan Moderasi Beragama pada Kurikulum Merdeka di SMK Negeri 1 Purworejo - Dhiya Ayu Tsamrotul Ihtiari; Abdul Aziz; Lu’luul Maknunah; Dhukhai Akhsani Nadiya (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
The purpose of this study was to determine the inculcation of the values of religious moderation in problem-based PAI learning through the implementation of an independent curriculum in class X PAI learning at SMK Negeri 1 Purworejo. This research is classroom action research whose workflow is repeated including planning, action, observation, reflection, re-planning, and so on until what is expected is achieved. The data collection technique used in the research is firstly, data on student learning outcomes is taken using a basic assessment of sharia insurance law at the end of each cycle meeting. Furthermore, data about reflection and changes that occur in the classroom are taken from the observation sheet. The data analysis technique was carried out with the collected data analyzed quantitatively and qualitatively. The data from the observations were analyzed qualitatively, while the data regarding the test results of students' cognitive knowledge were analyzed quantitatively. In this study, it is stated that the sharia insurance material which is PAI material in class X is carried out by giving problem assignments to students who are expected to be able to develop and find problems in sharia insurance material. Because in the practice of sharia insurance there are still many unresolved problems. The results of this study indicate that (1) The stages or syntax of PBL include five steps, namely providing orientation to the problem to students, organizing students, guiding individual or group investigations, developing and presenting work, analyzing and evaluating authentic problem solving processes. (2) the response of students to the given task is very positive. Students are enthusiastic in completing the given problem task, this task gives them experience, especially in terms of finding and solving problems